Network Coding aware Routing for Efficient Communication in Mobile Ad-hoc Networks - Prashanthi, V; Suresh Babu, D; V. Guru Rao, C (International Journal of Engineering and Technology, 2018)
Existing approach of routing protocols had only partial support towards energy efficiency. However, none of them had focused on considering network coding aware routing to reduce energy consumption. Majority of the existing solutions in literature to improve the communication performance of MANET has focused on minimum cost routing protocols. There are very less significant studies towards network coding in performing routing in MANET system. Therefore, it is totally unknown how network coding could be used to solve such issues. Throughput in wireless networks can be enhanced with the help of network coding. This approach also increases network lifetime in the cases of devices running on battery, such as wireless sensor nodes. Additionally, network coding achieves a reduction in the number of transmissions needed for transmission of a specific message through the network by making energy usage more efficient. Despite its benefits, however, network coding can have a negative impact on network lifetime if it is implemented excessively. Initially, to achieve the goal of improving throughput, reducing energy efficiency by reducing the number of broadcasting transmissions, a network coding model is created in this study and the MANET broadcast based on network coding is improved by the heuristic principle of Ant Colony Optimization. This study proposes the application of a network coding based dominating set approach to traditional routing protocols like adhoc on demand distance vector (AODV) as a solution to this issue. Coding gain of different topologies with different offer loads is evaluated using network coding. We discussed the performance of Alice-bob, cross, X, and wheel topologies using network coding. The study has paid particular attention to the trade-off between selection of paths compatible with network coding and network lifetime. The present study addresses this compromise that demonstrates that networks with energy restrictions are incompatible with the current network coding strategies based on throughput. One routing issue is attributed particular importance, namely, reduction of overall energy usage and improvement of individual node lifetime through effective routing of a series of traffic demands over the network. A range of analytical formulations is put forth to generate an optimal solution for the issue of multi-path routing. Results show that, by comparison to solutions without network coding, the suggested solutions improve energy efficiency while at the same time satisfying the specified lifetime restrictions.